2022
DOI: 10.3389/fonc.2022.921667
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Agents for Hepatocellular Carcinoma Imaging: Value and Progression

Abstract: Hepatocellular carcinoma (HCC) has the third-highest incidence in cancers and has become one of the leading threats to cancer death. With the research on the etiological reasons for cirrhosis and HCC, early diagnosis has been placed great hope to form a favorable prognosis. Non-invasive medical imaging, including the associated contrast media (CM)-based enhancement scan, is taking charge of early diagnosis as mainstream. Meanwhile, it is notable that various CM with different advantages are playing an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…Gd-EOB-DTPA-enhanced MRI can increase the minute lesion detection rate compared with extracellular contrast agent-enhanced MRI and multiphasic spiral CT, which is mainly achieved by increasing the contrast of images in the hepatobiliary phase (16)(17)(18)(19). The present study showed that all cases had improved in contrast evaluation indicators after contrast agent injection compared with the plain scan, which is consistent with previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…Gd-EOB-DTPA-enhanced MRI can increase the minute lesion detection rate compared with extracellular contrast agent-enhanced MRI and multiphasic spiral CT, which is mainly achieved by increasing the contrast of images in the hepatobiliary phase (16)(17)(18)(19). The present study showed that all cases had improved in contrast evaluation indicators after contrast agent injection compared with the plain scan, which is consistent with previously reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…Gd-EOB-DTPA-enhanced MRI can increase the minute lesion detection rate compared with extracellular contrast agent-enhanced MRI and multi-slice spiral CT, which is mainly achieved by increasing the contrast of images in the hepatobiliary phase ( 23 - 26 ). The present study showed that all cases had improved in contrast evaluation indices after contrast agent injection compared with the plain scan, which is consistent with previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in imaging technology have also facilitated the integration of artificial intelligence (AI) algorithms to aid in diagnosing and staging HCC. These AI-based approaches leverage machine learning techniques and large datasets to improve the accuracy and efficiency of HCC diagnosis, allowing for earlier detection and intervention [8]. The tumour typically starts as a small nodule and grows during the asymptomatic phase [3].…”
Section: Introductionmentioning
confidence: 99%